Beginning Android 4 Games Development - Zechner, Mario; Green,Robert; Safari Technical Books (New York : Apress L. P., 2011)
Annotation Beginning Android 4 Games Developmentoffers everything you need to join the ranks of successful Android game developers. You'll start with game design fundamentals and programming basics, and then progress toward creating your own basic game engine and playable game that works on Android 4.0 and earlier devices. This will give you everything you need to branch out and write your own Android games.The potential user base and the wide array of available high-performance devices makes Android an attractive target for aspiring game developers. Do you have an awesome idea for the next break-through mobile gaming title?Beginning Android 4Games Developmentwill help you kick-start your project.The book will guide you through the process of making several example games for the Android platform, and involves a wide range of topics:The fundamentals of Android game development targeting Android 1.5-4.0+ devicesThe Android platform basics to apply those fundamentals in the context of making a gameThe design of 2D and 3D games and their successful implementation on the Android platformWhat youll learnHow to set up and use the development tools for developing your first Android 4 or earlier version gameappThe fundamentals of game programming in the context of the Android platformHow to use the Android's APIs for graphics, audio, and user input to reflect those fundamentalsHow to develop two 2D games from scratch, based on the Canvas API and OpenGL ESHow to create a full-featured 3D gameHow to publish your games, get crash reports, and support your usersHow to complete your own playable 2D OpenGL gamesWho this book is forThis book is for people with a basic knowledge of Java who want to write games on the Android platform. It also offers information for experienced game developers about the pitfalls and peculiarities of the platform.Table of ContentsAndroid, the New Kid on the BlockFirst Steps with the Android SDKGame Development 101Android for Game DevelopersAn Android Game Development FrameworkMr. Nom Invades AndroidOpenGL ES: A Gentle Introduction2D Game Programming TricksSuper Jumper: A 2D OpenGL ES GameOpenGL ES: Going 3D3D Programming TricksDroid Invaders: the Grand FinaleAdvanced Techniques from Latest SDKPublishing Your Game.
Keywords: Electronic books